Combatting Covid-19 and the planned Reopening on 31 st May 2020 Take a ‘whole of the society approach’ - A statement from Bangladesh Health Watch (The Watch) (The Bangladesh Health Watch, 2020)
Bangladesh Health Watch, a citizens’ platform for improved accountability of the country’s healthcare system through evidence based policy review and citizen feedback, is deeply concerned at the recent steep increase in case numbers and continuation of unnecessary deaths due to Covid-19. On the contrary, Bangladesh remains at the bottom of the league table in South Asia in terms of the proportion of people tested for the disease. It is equally concerned at the failure of much of the population to adhere to basic prevention norms and the rising incidences of fear and stigma in the society. The Bangladesh Health Watch believes that in order to combat a crisis as large and complex as the Covid-19, the country needs a ‘whole of the society’ approach in which every group and individual is mobilized to fight the scourge, as we did in the War of Liberation. Unfortunately this is sadly absent. The Watch believe that the social and scientific aspects of the planned ‘reopening’ on 31 st May 2020 and its likely consequences have not been duly considered.